Analyses of Ferrous and Ferric State in DynabiTab Using Mössbauer Spectroscopy - Young Rang Uhm; Jae Cheong Lim; Sang Mu Choi (International Journal of Analytical Chemistry)
Antianemic medicament ferrous gluconate, ferrous fumarate, and a Dynabi tablet with a basic iron bearing ingredient were studied with the use of Mössbauer spectroscopy. Room temperature spectra of ferrous gluconate gave clear evidence that the two phases of iron were present: ferrous (Fe2+) as a major one with a contribution at and above 91 a.u.% and ferric (Fe3+) whose contribution was found to be ~9 a.u.%. In the case of ferrous fumarate, a single phase was measured corresponding to ferrous (Fe2+) state. A Dynabi tablet consists of ferrous fumarate and ferrous fumarate. The ferric phase in ferrous gluconate is able to be reached about ~3.6 a.u.% in a tablet.